A conceptual chemical looping combustion power system design in a power-to-gas energy storage scenario. (12th April 2019) - Ajiwibowo, Muhammad W.; Darmawan, Arif; Aziz, Muhammad
Abstract: Increasing global energy demand and the continued reliance on non-renewable energy sources, especially in developing countries, will cause continued increases in greenhouse gas emissions unless alternative electricity generation methods are employed. Although renewable energy sources can provide a clean way to produce electricity, the intermittent nature of many existing renewable energy sources, such as energy from the wind or sun, can cause instability in the energy balance. Energy storage systems such as power-to-gas may provide a clean and efficient way to store the overproduced electricity. In this work, a power-to-gas energy storage system coupled with a chemical looping combustion combined-cycle power generation system is proposed to provide base and intermediate load power from the unused electricity from the grid. Enhanced process integration was employed to achieve optimal heat and exergy recovery. The simulation results using ASPEN Plus V8.8 suggest that electric power generation with an overall energy efficiency of 56% can be achieved by using a methane chemical looping combustion power generation process with additional hydrogen produced from a solid oxide electrolysis cell. The proposed system was also evaluated to further improve the system's total energy efficiency by changing the key operating parameters. Highlights: An efficient energy system of a power-to-gas energy storage is proposed. The system comprises SOEC and chemical looping combustion (CLC) combined cycle power. Three types of metal oxides are investigated during CLC process. The proposed system can separate CO2 directly via condensation due to the clean combustion. The proposed system can achieve high efficiency about 56%.